The Impact of Internet-Based Selling Technology: A Hybrid Growth Theory Perspective with Cross-Model Inference - HO, S. C. (Institutional Knowledge at Singapore Management University, 2011)
Innovations associated with information and communication technology (ICT) have opened up new opportunities for the global economy and ushered in the age of e-commerce. Our objective in this research is to explore the role of Internet-based selling technology, which acts as technology infrastructure for B2C e-commerce growth at the country level. This study proposes the use of a new hybrid growth theory approach as the theoretical basis for examining exogenous and endogenous factors that influence e-commerce growth over time. We estimate three different models to evaluate their explanatory capabilities. We investigate a panel-corrected feasible generalized least squares regression that incorporates the direct effects of country-level variables. We also specify an endogeneity-adjusted two-stage least squares model and estimate it with an embedded technology adoption function in a simultaneous equation model. This permits the analysis of the relevance of IT infrastructure, as well as reverse causality between e-commerce growth and Internet-based selling technology. We test these models using archival data for four different regions, based on either 24 or 42 countries around the world, depending on the data requirements of the models. Our empirical tests evaluate quasi-production environmental inputs, in which technology determines the environment of production of e-commerce services. Our main finding is that both endogenous variables (e.g., Internet user penetration, capital invested in telecommunication) and exogenous variables (international openness) drive the GDP-normalized level of B2C e-commerce revenues over time. A second main finding is that it is useful to include an embedded technology adoption function in a modeling specification for growth, since growth is founded on the availability of relevant IT infrastructure that is made possible by the availability of venture capital. In addition, B2C e-commerce revenue growth and venture capital also contribute to the adoption of Internet-based selling technology. We discuss our overall approach for the interpretation of the strength of our main findings, as well as the policy implications, and why our hybrid growth theory approach is useful.